Analisis Pengaruh Pengetahuan dan Sikap T erhadap Perilaku Membuang Sampah - Al- Bahra (STIKes RSPAD RSPAD Gatot Soebroto, 2018)
Human life can not be separated from the environment, both the natural environment and social environment. In environmental issues, humans have a very important role. There are many human activities that directly or indirectly have an impact on environmental damage, one of which is the activity of littering in any place. The purpose of this study was to determine the effect of knowledge and attitudes on trash disposal behavior in Muhammadiyah 34 elementary school students. This research uses quantitative correlation research with cross sectional study approach. The population in this study were all elementary school students with a population of 301 in the 2017 school year. The sample in this study was 83 people using the formula proposed by Nursalam. The results showed that students of Muhammadiyah 34 Elementary School who behaved poorly in disposing trash 46 (55.4%) respondents, with male gender as many as 38 (45.8%) respondents. Respondents who have poor knowledge 43 (51.8%) and who have negative attitudes 50 (60.2%) respondents. Inadequate availability of facilities for trash bins in schools 42 (50.6%), and teacher support that lacks support for 42 (50.6%) respondents. The results of the bivariate analysis with the chi square test of the variables studied showed that there was a relationship between gender, knowledge, attitudes, teacher support and the availability of trash facilities and the behavior of disposing garbage to the Muhammadiyah 34 Elementary School students. Keywords: Knowledge, Attitude, Behavior, Trash.